Combined Dexamethasone Suppression-Corticotropin-Releasing Hormone Stimulation Test in Studies of Depression, Alcoholism, and Suicidal Behavior - Leo Sher (The Scientific World Journal)
The hypothalamic-pituitary-adrenal (HPA) axis controls the secretion of corticotropin-releasing hormone (CRH), corticotropin (adrenocorticotropic hormone, ACTH), and cortisol. The dexamethasone suppression test (DST) is the most frequently used test to assess HPA system function in psychiatric disorders. Patients who have failed to suppress plasma cortisol secretion, i.e., who escape from the suppressive effect of dexamethasone, have a blunted glucocorticoid receptor response. After CRH became available for clinical studies, the DST was combined with CRH administration. The resulting combined dexamethasone suppression-corticotropin-releasing hormone stimulation (DST–CRH) test proved to be more sensitive in detecting HPA system changes than the DST. There is a growing interest in the use of the DEX-CRH test for psychiatric research. The DEX-CRH test has been used to study different psychiatric conditions. Major depression, alcoholism, and suicidal behavior are public health problems around the world. Considerable evidence suggests that HPA dysregulation is involved in the pathogenesis of depressive disorders, alcoholism, and suicidal behavior. Over the past 2 decades, there has been a shift from viewing excessive HPA activity in depression as an epiphenomenon to its having specific effects on symptom formation and cognition. The study of HPA function in depression, alcoholism, and suicidal behavior may yield new understanding of the pathophysiolgy of these conditions, and suggest new approaches for therapeutic interventions. The combined DEX-CRH test may become a useful neuroendocrinological tool for evaluating psychiatric patients.